Hydroxytyrosol-rich extract from olive juice as an additive in gilthead sea bream juveniles fed a high-fat diet: Regulation of somatic growth - Balbuena-Pecino, Sara; Montblanch, Manel; García-Meilán, Irene; Fontanillas, Ramon; Gallardo, Ángeles; Gutiérrez, Joaquim; Navarro, Isabel; Capilla, Encarnación (Frontiers in Physiology, 2022)
The dietary inclusion of plant-based products in fish feeds formulation is required for the sustainable development of aquaculture. Moreover, considering functional diets, hydroxytyrosol, one of the major phenolic compounds found in olives (Olea europaea), has been identified as a potential candidate to be used in the aquafeeds industry due to its health promoting abilities. The aim of this study was to evaluate the effects of the inclusion of an olive juice extract rich in hydroxytyrosol as an additive (0.52 g HT/kg feed) in a high-fat (24% lipids) diet in gilthead sea bream (Sparus aurata) juveniles. Moreover, the experimental diets, with or without the extract, were administered daily at a standard (3% of total biomass in the tank) or restricted ration (40% reduction) for 8-9 weeks. Growth and biometric parameters, insulin-like growth factor 1 (IGF-1) plasma levels and growth hormone/IGF axis-, myogenic- and osteogenic-related genes expression in liver, white muscle and/or bone were analyzed. Moreover, in vitro cultures of vertebra bone-derived cells from fish fed the diets at a standard ration were performed at weeks 3 and 9 to explore the effects of hydroxytyrosol on osteoblasts development. Although neither body weight or any other biometric parameter were affected by diet composition after 4 or 8 weeks, the addition of the hydroxytyrosol-rich extract to the diet increased IGF-1 plasma levels, regardless of the ration regime, suggesting an anabolic condition. In muscle, the higher mRNA levels of the binding protein igfbp-5b and the myoblast fusion marker dock5 in fish fed with the hydroxytyrosol-rich diet suggested that this compound may have a role in muscle, inducing development and a better muscular condition. Furthermore in bone, increased osteogenic potential while delayed matrix mineralization after addition to the diet of the olive juice extract was supported by the upregulated expression of igf-1 and bmp4 and reduced transcript levels of osteopontin. Overall, this study provides new insights into the beneficial use of hydroxytyrosol as a dietary additive in gilthead sea bream functional diets to improve muscle-skeletal condition and, the aquaculture industry.